Minister of International Development and La Francophonie Mandate Lett er (November 12, 2015) (Office of the Prime Minister, 2015)
Dear Minister:I am honoured that you have agreed to serve Canadians as Minister of International Development and La Francophonie. You will b e part of a strong team of ministers led by the Minister of Foreign Af fairs.